2016
DOI: 10.1002/etc.3338
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 2,4‐dinitroanisole in the earthwormEisenia fetidafrom chemically spiked and aged natural soils

Abstract: An initiative within the US military is targeting the replacement of traditional munitions constituents with insensitive munitions to reduce the risk of accidental detonation. The bioavailability and bioaccumulative potential of the insensitive munitions compound 2,4-dinitroanisole (DNAN) to Eisenia fetida was assessed in soils with different geochemical characteristics. Prior to exposure, soils were chemically spiked with DNAN and aged for 1 wk or 29 wk. Transformation products 2- and 4-amino-nitroanisole (2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…Reductive transformation of DNAN and soil concentration decrease over time are consistent with previous investigations with DNAN (Dodard et al 2013;Richard and Weidhass 2014;Lotufo et al 2016;Temple et al 2018) and also with TNT, a related nitroaromatic compound (see Simini et al 2013). The DNAN strongly adsorbs to soil and is (bio)transformed via reduction of nitro groups to amino groups to form a variety of products, including 2-ANAN, 4-ANAN, and 2,4-diaminoanisole (DAAN; Dontsova et al 2014;Hawari et al 2015;Lotufo et al 2016;Olivares et al 2016;Indest et al 2017;Temple et al 2018). The preferential reduction to 2-ANAN we observed further corroborates previous evidence for regioselective reduction of the ortho-nitro group (Hawari et al 2015;Lotufo et al 2016;Olivares et al 2016;Arthur et al 2017;Temple et al 2018).…”
Section: Preliminary Evaluation Of Dnan Uptake From Soil By Earthwormssupporting
confidence: 91%
See 2 more Smart Citations
“…Reductive transformation of DNAN and soil concentration decrease over time are consistent with previous investigations with DNAN (Dodard et al 2013;Richard and Weidhass 2014;Lotufo et al 2016;Temple et al 2018) and also with TNT, a related nitroaromatic compound (see Simini et al 2013). The DNAN strongly adsorbs to soil and is (bio)transformed via reduction of nitro groups to amino groups to form a variety of products, including 2-ANAN, 4-ANAN, and 2,4-diaminoanisole (DAAN; Dontsova et al 2014;Hawari et al 2015;Lotufo et al 2016;Olivares et al 2016;Indest et al 2017;Temple et al 2018). The preferential reduction to 2-ANAN we observed further corroborates previous evidence for regioselective reduction of the ortho-nitro group (Hawari et al 2015;Lotufo et al 2016;Olivares et al 2016;Arthur et al 2017;Temple et al 2018).…”
Section: Preliminary Evaluation Of Dnan Uptake From Soil By Earthwormssupporting
confidence: 91%
“…Lotufo et al (2016) reported E. fetida BAF values for 4 different soils that, when converted to dry weight basis (Supplemental Data, Table S4), were overall in the same range as the BAF values derived for SSL soil in the present study (Tables 1 and 2). Following amendment with DNAN, the soils also equilibrated for 7 d in Lotufo et al (2016). The SumDNAN BAF values determined in the present study were also similar to the BAF values reported for TNT (5.0 kg/kg dry wt), 2-aminodinitrotoluene (5.1 kg/kg dry wt), and 4-aminodinitrotoluene (6.4 kg/kg dry wt; Lachance et al 2004).…”
Section: Accumulation Factor Determination For Dnan In Soilsupporting
confidence: 75%
See 1 more Smart Citation
“…As a nitroaromatic compound, DNAN is effectively adsorbed to phyllosilicate clay surfaces by nitro group complexation with exchangeable cations (Linker et al, 2015) and it also exhibits an affinity for binding to natural organic matter (NOM) (Lotufo et al, 2016). In contrast, the high aqueous solubility, low NOM affinity (Mark et al, 2016), and anion exclusion from phyllosilicate clay surfaces observed for NTO (Linker et al, 2015) raises particular concern about potential ground water contamination (Le Campion et al, 1999;Pizzigallo et al, 1998;Smith and Cliff, 1999;Spear et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient contact time between IM compounds and the sediment prior to conducting toxicity testing should be provided. Increased contact time, or aging, affects the chemical composition, bioavailability, and toxicity of organic compounds in soils and sediments, including munitions constituents (Northcott and Jones 2000;Conder et al 2004;Kuperman et al 2013;Lotufo et al 2016). This SOP provides a method for spiking IM compounds with sediments that is solvent-free, and provides adequate equilibration time prior to use in toxicity testing.…”
Section: Introductionmentioning
confidence: 99%